Regional Financial Independence and Audit Opinion Quality Effects on Capital Expenditure in Papua - Putra Agung Dwijaya; Elsyan R. Marlissa; Yundy Hafizrianda (Penerbit Goodwood, 2026)
Purpose: This study examines the effect of regional financial performance, proxied by regional financial independence, and financial report quality, proxied by the audit opinion of Indonesia's Supreme Audit Agency or Badan Pemeriksa Keuangan (BPK), on capital expenditure among regencies and cities in Papua Province, individually and jointly.Research Methodology: The study used secondary panel data covering 8 regencies and 1 city in Papua Province over the 2019-2024 period, drawn from BPK audit reports on regional government financial statements, yielding 54 observations. Data were analyzed with panel data regression, selected among the common effect, fixed effect, and random effect specifications through the Chow, Hausman, and Lagrange Multiplier tests, followed by classical assumption testing and hypothesis testing using EViews.Results: Regional financial independence had a negative and significant effect on capital expenditure, financial report quality had a positive but not significant effect, and the two variables jointly did not have a significant effect, explaining only a small share of the variation in capital expenditure.Conclusions: Rising fiscal independence in Papua's regencies and cities has not translated into higher capital spending, a pattern consistent with agency-theory concerns about how additional own-source revenue is used.Limitations: The two-variable model, the nine-region sample, and the six-year window limit the explanatory power and generalizability of the findings.Contributions: The study extends agency theory to a fiscally distinctive Papuan setting and identifies capital expenditure determinants that warrant further investigation beyond financial independence and audit opinion.